Development of paediatric non-stage prognosticator guidelines for population-based cancer registries and updates to the 2014 Toronto Paediatric Cancer Stage Guidelines. Issue 9 (September 2020) - Gupta, Sumit; Aitken, Joanne; Bartels, Ute; Bhakta, Nickhill; Bucurenci, Mihaela; Brierley, James D; De Camargo, Beatriz; Chokunonga, Eric; Clymer, Jessica; Coza, Dana; Fraser, Chris; Fuentes-Alabi, Soad; et al.
Summary: Population-based cancer registries (PBCRs) generate measures of cancer incidence and survival that are essential for cancer surveillance, research, and cancer control strategies. In 2014, the Toronto Paediatric Cancer Stage Guidelines were developed to standardise how PBCRs collect data on the stage at diagnosis for childhood cancer cases. These guidelines have been implemented in multiple jurisdictions worldwide to facilitate international comparative studies of incidence and outcome. Robust stratification by risk also requires data on key non-stage prognosticators (NSPs). Key experts and stakeholders used a modified Delphi approach to establish principles guiding paediatric cancer NSP data collection. With the use of these principles, recommendations were made on which NSPs should be collected for the major malignancies in children. The 2014 Toronto Stage Guidelines were also reviewed and updated where necessary. Wide adoption of the resultant Paediatric NSP Guidelines and updated Toronto Stage Guidelines will enhance the harmonisation and use of childhood cancer data provided by PBCRs.